PARTITIONING, BIOAVAILABILITY AND ORIGIN OF HEAVY METALS FROM THE NADOR LAGOON SEDIMENTS (MOROCCO) AS A BASIS FOR THEIR MANAGEMENT - González I.; Águila E.; Galán E. (My University, 2007)
Nador Lagoon sediments show low trace element concentrations, and, in relation to the lagoon geochemical baseline, only some anomalies for As, Cd, Cu and Pb in the NW of the lagoon deserve to be outstanding. The distribution of major, minor and trace elements in the lagoon allows a breakdown in four zones. Between “Beni Ensar” and “Atelouane” (zone A), a quite confined zone rich in organic matter and S, the most important trace-element anomalies (As, Cd, Co, Cu, Mn, Pb, Zn) were found, mainly around industry and old mining activities. In the surrounding of the city of Nador (zone B), the anomalies correspond to Mn, Cu and Zn. The coastal barrier and Kebdana channel (zone C) show moderately concentrations of Cd, Cr and Ni at specific sites. The less polluted area is the SE of the lagoon (zone D), with no outstanding anomaly. In lagoon sediments, metal bioavailability is very low. The metal partitioning patterns show that Cu, Pb and Zn present a low availability because they are bounded to the residual, non-mobile phases of the sediments. Only in some sites, the fraction was associated with organic matter, which could be liberated easily. Arsenic is concentrated in both the residual phases and the organic matter, the latter being more available. Cadmium is mainly concentrated in some samples in the interchangeable fraction, which could be considered as a potentially toxic element because it is easily released. Concerning the origin of these trace elements, those found in zone A correspond mostly to a natural source by weathering of mount Gourougou volcanic rocks (As, Co, Cu, Pb and Zn), and to an anthropogenic origin (Cd) owing to the presence of industry and old mines. In zone B, contributions of Cu and Zn enter the lagoon through soil weathering and river-borne, and as anthropogenic pollution from urban wastes. In zone C the most important pollutant is Cd deduced to be of anthropogenic origin from the close industry and intensive agriculture area. In spite of the intense socio-economic activities developed in the Nador Lagoon (agriculture, industry, fishing, tourism) trace element concentrations in the sediments are low and with scarce bioavailability. Only the NW sector is relativity polluted because of geogenic features.
Keywords: HEAVY METALS; GEOCHEMISTRY; BIOAVAILABILITY; GEOACCUMULATION INDEX; LAGOON SEDIMENTS; NADOR; MOROCCO